Handball training in u-21 and adult teams: differences and similarities - Pombo Menezes, R.; Longarela Pérez, B.; Rafaela Galatti, L. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2020)
Handball coaches aim to develop different players’ skills, using different teaching approaches. The aim of this work was to identify the differences and methodological proximity between the junior and adult teams of women’s handball. Six handball coaches were interviewed and the speeches were analyzed using the Collective Subject Discourse method. The coaches mentioned similar characteristics of both teams, and point out the increase in specificity and results collection from the junior team; and the main differences between these teams are related to the competitive experiences and the magnitude of the results charged. Coaches have been using similar teaching approaches mainly because the integration between the teams and the search for expressive results in competitions. Although coaches believe that there is a need for more competitive experiences for women players, there is a charge for the content with which they are supposed to have contact throughout their entire training process.